Investigating the role of internal layout of magnetic field-generating equipment on workers' exposure at power substations. Issue 1 (2nd January 2021) - Hosseini, Monireh; Farhang Matin, Laleh; Monazzam, Mohammad Reza; Khosroabadi, Hossein
Abstract : Introduction . This research is an attempt to show the role of interior layout of equipment in generating magnetic fields. Materials and methods . The levels of an extremely low-frequency magnetic field were measured in accordance with Standard No. IEEE 644:1994 in three substations and a control building in a petrochemical power plant in southern Iran. Then, workers' occupational exposure (time-weighted average [TWA]) was calculated and the sources of maximum magnetic field generation at each place were identified. Their interior design was changed to achieve the optimal layout of equipment subsequently; the workers' TWA was recalculated for the new situation. Results . The obtained results showed that electrical engineers and technicians were exposed to the maximum TWA of 10.14 μT. The operators in the control room were exposed to the lowest TWA of 0.84 μT. The results also showed that after the change of interior design and proper layout design of the equipment in the substations, the TWA was reduced by 0.73 μT. Conclusion . The research findings revealed that the most harmonious arrangement of equipment in an industrial unit plays a major role in reducing the exposure of workers to magnetic fields and ultimately increases the level of their health in the workplace.